National surveillance for type 1, type 2 diabetes and prediabetes among children and adolescents: a population-based study (SAUDI-DM). Issue 11 (17th June 2015) - Al-Rubeaan, Khalid
Abstract : Background: There is a paucity of data on the national prevalence of diabetes and prediabetes among youth. The Saudi Abnormal Glucose Metabolism and Diabetes Impact Study (SAUDI-DM) was used to assess the prevalence of type 1 and type 2 diabetes as well as impaired fasting glucose (IFG) among children and adolescents. Methods: Sociodemographic, anthropometric and clinical data were collected through a nationwide household randomly selected 23 523 children and adolescents aged ≤18 years. Known participants with diabetes were classified according to their diabetes type, while participants without diabetes were subjected to fasting plasma glucose assessment and patients with diabetes were identified using the American Diabetes Association (ADA) criteria. All the studied participants were tested for lipid parameters. Multivariate logistic regression analysis was used to assess different risk factors. Results: The overall prevalence of diabetes was 10.84%, of which 0.45% were known type 1 and type 2 patients with diabetes and 10.39% were either newly identified cases of diabetes (4.27%) or IFG (6.12%) with more than 90% of the participants with diabetes being unaware of their disease. The prevalence of known type 1 and type 2 diabetes as well as the newly identified cases was higher than what has been reported internationally. Age, male gender, obesity, urban residency, high family income and presence of dyslipidaemia were found to be significant risk factors for diabetes and IFG. Conclusions: Diabetes and IFG are highly prevalent in this society with the majority of the patients being unaware of their disease, which warrants urgent adoption of early detection, treatment and prevention programmes.